Efficacy of DA-7218, a new oxazolidinone prodrug, in the treatment of experimental actinomycetoma produced by nocardia brasiliensis - Espinoza González, Nelly Alejandra; Welsh Lozano, Oliverio; De Torres, Noemi Waksman; Cavazos Rocha, Norma Cecilia; Ocampo Candiani, Jorge; Said Fernández, Salvador; Lozano Garza, Gerardo; Choi, Sung Hak; Vera Cabrera, Lucio (2008)
Two recently synthesized oxazolidinones: (R)-3-(4-(2-(2-methyltetrazol-5-yl)- pyridin-5-yl)-3-fluorophenyl)-5-hydroxymethyloxazolidin-2-one (DA-7157) and its corresponding pro-drug (R)-3-(4-(2-(2-methyltetrazol-5-yl)-pyridin-5-yl)-3-fluorophenyl)- 2-oxo-5-oxazolidinyl) methyl disodium phosphate (DA-7218), have shown very good activity against several Gram positive bacteria, including Nocardia and Mycobacterium. In the present work we evaluated the therapeutic in vivo effects of DA-7218 on Nocardia brasiliensis. We first determined the plasma concentration of the prodrug in BALB/c mice using several doses and then tested its activity in an in vivo experimental actinomycetoma murine model. At the end of treatment, there was a statistically significant difference between the three drug receiving groups (25, 12.5 and 5 mg/kg) and the control group (saline solution) (p=0.001), proving that DA-7218 is effective for the treatment of experimental murine actinomycetoma. This compound could be a potential option for patients affected with mycetoma by Nocardia brasiliensis.